Fate of large-scale structure in modified gravity after GW170817 and GRB170817A - Amendola, Luca; Sawicki, Ignacy (Physical review letters, 2018)
The coincident detection of gravitational waves (GW) and a gamma-ray burst from a merger of neutron stars has placed an extremely stringent bound on the speed of GWs. We showed previously that the presence of gravitational slip (η) in cosmology is intimately tied to modifications of GW propagation. This new constraint implies that the only remaining viable source of gravitational slip is a conformal coupling to gravity in scalar-tensor theories, while viable vector-tensor theories cannot now generate gravitational slip at all. We discuss structure formation in the remaining viable models, demonstrating that (i) the dark-matter growth rate must now be at least as fast as in general relativity (GR), with the possible exception of that beyond the Horndeski model, and (ii) if there is any scale dependence at all in the slip parameter, it is such that it takes the GR value at large scales. We show a consistency relation that must be violated if gravity is modified.